Peningkatan Potensi Desa Wisata Melalui Pemberdayaan Masyarakat Di Desa Perlang, Kabupaten Bangka Tengah - Chery Tamisha; Annisa Fitriani; Silvia (Universitas Bangka Belitung, 2023)
For four months, Perlang Village, Lubuk Besar District, Central Bangka Regency, became a place of service for the KKNT program for Bangka Belitung University students. There are two types of these activities: non-programmed work programs and programmed work programs. Training is provided as part of community service activities in Perlang village with the aim of improving the economy and creativity of the community, especially MSMEs. The next task is cultivating palm mushrooms and choosing a new snorkeling location for village visitors. Additional activities carried out are activities that are based on meeting community needs, such as carrying out social service, participating in independence events and being a ceremonial officer, taking part in the Lake Pading 2 festival, delivering educational material and teaching in line, providing counseling at Posyandu, and creating photo spots.